From bio-electronics to anthropology – the development of the anthropological problems in the work of Włodzimierz Sedlak - Struzik, Elżbieta (Folia Philosophica, 2002)
The present article shows the development of anthropological reflection in the scholarly and philosophical works by Włodzimierz Sedlak. The process of shaping the field of research proper to naturalist anthropology has been presented against the background of reflections on the bio-electronic vision of life. It is exactly against this background that the concepts of homo electronicus and of homo comicus, with the problems peculiar to them, can come into being. The naturalistic vision of man may serve as a point of departure for analyses belonging already to philosophical anthropology. The problems typical of the philosophical analysis implies questions of a metaphysical nature. Within the framework of theological anthropology, the problem of the relationship between man and God. Reflections on this subject are characteristic of Christian evolutionism and personalism.